2021
DOI: 10.3390/molecules26040951
|View full text |Cite
|
Sign up to set email alerts
|

Opuntia ficus-indica (L.) Mill.: A Multi-Benefit Potential to Be Exploited

Abstract: Consumer interest in foods with enhanced nutritional quality has increased in recent years. The nutritional and bioactive characterization of fruits and their byproducts, as well as their use in the formulation of new food products, is advisable, contributing to decrease the global concerns related to food waste and food security. Moreover, the compounds present in these raw materials and the study of their biological properties can promote health and help to prevent some chronic diseases. Opuntia ficus-indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 82 publications
3
53
1
2
Order By: Relevance
“…However, little interest has been given to the use of the fruit seeds because the body is unable to digest them and therefore to benefit from their constitutions. Several scientific studies have been interested in studying the different vegetative parts (pulp, seed, peel, and cladode) of these two species to assess or confirm their beneficial biological effects on various diseases [7,8]. Over the last few years, researchers have been interested in studying the seed oils of these two Opuntia species and have found that they are rich in very active molecules [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, little interest has been given to the use of the fruit seeds because the body is unable to digest them and therefore to benefit from their constitutions. Several scientific studies have been interested in studying the different vegetative parts (pulp, seed, peel, and cladode) of these two species to assess or confirm their beneficial biological effects on various diseases [7,8]. Over the last few years, researchers have been interested in studying the seed oils of these two Opuntia species and have found that they are rich in very active molecules [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it is not surprising that O. ficus-indica constitutes part of the core species in the global network. O. ficus-indica was first introduced to Europe via Spain during the fifteenth century, and it has been cultivated in many parts of the world for various purposes, including carminic acid extraction from Dactylopius coccus Costa, 1835 [ 18 , 81 ]. In this regard, PadrĂłn et al [ 20 ] found that O. maxima is an invader species that behaves as a core species in native communities, where it becomes naturalized.…”
Section: Discussionmentioning
confidence: 99%
“…However, some Opuntia species were introduced to other continents after the Spanish conquest [ 12 , 13 , 14 ] due to their traditional uses as medicinal plants, fruits, vegetables, dyes, food ingredients, and forage, among others [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although these cladodes have been used as a traditional treatment for T2DM in Mexico [22], the use of Opuntia spp. as a basis of functional food products for the management of a range of health conditions has been proposed only relatively recently [23][24][25].…”
Section: Introductionmentioning
confidence: 99%